Equity and trusts - Hudson, Alastair (Abingdon, Oxon [UK] ; New York : Routledge-Cavendish, 2012)
"Alastair Hudson's Equity and Trusts is an ideal textbook for underg raduate courses on the law of trusts and equitable remedies. It provide s a clear, current and comprehensive account of the subject through whi ch the author's enthusiasm and expertise shine through, helping to brin g to life an area of the law which students often find challenging.Begi nning with the core principles, Professor Hudson reinforces the key poi nts by means of clear examples throughout each chapter, helping student s to build and develop their own knowledge of equity and trusts. A set of lively, discursive essays reflecting on the law then begin to outlin e the broader political, social and economic context of the subject and encourage the reader to begin to engage with their own critical analys is. Although aimed at Students, Alastair Hudson is also the author of a practitioner text and brings that experience and detail to Equity and Trusts, which has now come to be cited in courts across different juris dictions.The seventh edition is supported by a companion website which includes:over 50 short podcast lectures by the author discussing and cl arifying key topics from within the book, which cover an entire course; a set of brief video documentaries filmed on location which provide co ntext and bring to life selected key topics; a brief introductory video presentation from the author introducing the viewer to the subject of Equity and Trusts and to the book in particular"--
"Alastair Hudson's Equity and Trusts is an ideal textbook for underg raduate courses on the law of trusts and equitable remedies. It provide s a clear, current and comprehensive account of the subject through whi ch the author's enthusiasm and expertise shine through, helping to brin g to life an area of the law which students often find challenging. Beg inning with the core principles, Professor Hudson reinforces the key po ints by means of clear examples throughout each chapter, helping studen ts to build and develop their own knowledge of equity and trusts. A set of lively, discursive essays reflecting on the law then begin to outli ne the broader political, social and economic context of the subject an d encourage the reader to begin to engage with their own critical analy sis. Although aimed at Students, Alastair Hudson is also the author of a practitioner text and brings that experience and detail to Equity and Trusts, which has now come to be cited in courts across different juri sdictions. The seventh edition is supported by a companion website whic h includes: over 50 short podcast lectures by the author discussing and clarifying key topics from within the book, which cover an entire cour se; a set of brief video documentaries filmed on location which provide context and bring to life selected key topics; a brief introductory vi deo presentation from the author introducing the viewer to the subject of Equity and Trusts and to the book in particular"--
Keywords: Equity -- England; Trusts and trustees -- England